Capturing nonclassical C70 with double heptagons in low-pressure combustion. Issue 70 (17th August 2022) - Xie, Fang-Fang; Chen, Zuo-Chang; Zhang, Min; Xie, Xiao-Ming; Chen, Ling-Fang; Tian, Han-Rui; Deng, Shun-Liu; Xie, Su-Yuan; Zheng, Lan-Sun
Abstract : A novel nonclassical fullerene dihept-C70 H6, captured from low-pressure combustion, is considered to be vital evidence for the further study of heptafullerenes. Abstract : A double–heptagon–containing C70 H6 (dihept-C70 H6 ) was isolated and unambiguously characterized in the soot of low-pressure combustion, which shares the identical heptagonal cage as dihept-C70 Cl6 previously identified in the products of carbon arc, and thus represents the first nonclassical fullerene isolable in both carbon arc and combustion.